Sickle cell disease in the tribal population attending tertiary referral centre in Surguja district of Chhattisgarh - Mallik, Mahasweta; Singh, Alka; Mallick, Sujata (International Journal of Medical Research and Review, 2016)
Background: sickle cell anaemia is a haemoglobin disorder which is autosomal recessive. As it is inherited disorder it is prevalent more in tribal population of India. Surguja district of Chhattisgarh also has a predominance o of tribal population. Aim: Aim of this study is to find the incidence of sickle cell disease in the tribal population attending the tertiary referral hospital of surguja district. Material and method: This is a retrospective study of a span of 3years from April 2013 to March 2016. A total of 5489 anaemic patients were tested. Result: out of 5489 anaemic patients 399 were positive for sickle cell. Conclusion: Education and counselling should be done to prevent sickle cell disease among the tribal of surguja district of chattisgarh.